Elections to the European Parliament May 26, 2019: Characteristics of the Election Campaign in Germany - Ekaterina Timoshenkova (Научно-аналитический вестник Института Европы РАН, 2019)
The paper analyzes the preparation of German political parties for the elections to the European Parliament in 2019. The author identifies the main patterns of electoral behavior, studies the election programs and strategies of the parties represented in the Bundestag. This allows us to formulate a forecast of the election results in Germany and how they will affect the overall balance of power in the European Parliament. Particular attention is paid to the analysis of the positions of government and opposition parties in relation to Russia, as well as the prospects of German politicians for key positions in Brussels after the elections.